Use of the campus of Universidade Federal da Grande Dourados as a refuge for birds of fragment of the Mata Azulão in Dourados, Mato Grosso do Sul State, Brazil - DOI: 10.4025/actascibiolsci.v31i4.4548 - Catian, Gisele (2009)
This paper aimed to verify the day-active birds in the area of the campus of the Universidade Federal da Grande Dourados, Dourados – Mato Grosso do Sul State, which is next to the fragment of the Atlantic forest of Mata do Azulão, Dourados – Mato Grosso do Sul State. There were 65 hours of visual and audio observations during the period from April to September 2007. Seventy-two species were observed, which were gradually emerging on campus. This shows that the campus is used as a refuge for birds of fragment of the Mata Azulão and suggests that further work with an even greater sampling effort considering the seasonal nature be conducted